Mechanical characterization and comparison of energy storage and return prostheses. (March 2017) - Rigney, Stacey M.; Simmons, Anne; Kark, Lauren
Highlights: Proposes a new method for assessing energy storage and return prostheses. Finite element model includes 'stick' and 'slip' experimental friction conditions. Analysis of Vari-flex Modular, Flex-foot Cheetah, Cheetah Xtreme and 1E90 Sprinter. Prosthesis overall stiffness correlates negatively with energy stored and lost. Energy efficiency may be over-estimated by link-segment models. Abstract: The suitability of finite element analysis (FEA) for standardizing the mechanical characterization of energy storage and return (ESAR) prostheses was investigated. A methodology consisting of both experimental and numerical analysis was proposed and trialed for the Vari-flex ® Modular TM, Flex-foot Cheetah and Cheetah Xtreme by Össur ® and a 1E90 Sprinter by Ottobock ® . Gait analysis was conducted to determine suitable orientation angles for non-destructive testing (NDT) of the ESAR prostheses followed by a quasi-static inverse FEA procedure within COMSOL Multiphysics ®, where the NDT conditions were replicated to determine the homogenized material properties of the prostheses. The prostheses' loading response under bodyweight for an 80 kg person was then simulated, using both Eigenfrequency and time-dependent analysis. The apparent stiffness under bodyweight was determined to be 94.7, 48.6, 57.4 and 65.0 Nmm −1 for the Vari-flex ® Modular TM, Flex-foot Cheetah, Cheetah Xtreme and 1E90 Sprinter, respectively. Both the energy stored and returned by the prostheses varied negatively with stiffness, yet the overall efficiency of the prostheses were similar, at 52.7, 52.0, 51.7 and 52.4% for the abovementioned prostheses. The proposed methodology allows the standardized assessment and comparison of ESAR prostheses without the confounding influences of subject-specific gait characteristics. Graphical abstract: